The Analysis of Relationship Between Green Attitudes and Students’ Literacy Ability Toward Environment - Iwan Henri Kusnadi; Made Ayu Anggreni; Wa Ode Riniati; Sardjana Orba Manullang; Muhammad Ridhwan (Journal on Education, 2023)
This study compared the students' environmental care attitudes and environmental literacy skills in two schools. This study uses an ex-post facto research strategy and a quantitative methodology. Purposive sampling was used to sample the science class population, and data were collected by dividing the environmental care attitude surveys and environmental literacy test instruments. Using an SPSS, the data were examined using the independent sample t-test. The study's findings demonstrate that pupils' environmental literacy for schools X (65.50) and Y (62.09) meet good requirements. The criteria for student attitudes toward the environment are quite good; schools X and Y score 58.56 and 58.86, respectively. The results of the hypothesis test indicate a difference in students' environmental literacy but no difference in their attitude toward the environment between the two schools, with a sig. of 0.020 < 0.05 for environmental literacy and a sig. of 0.944 > 0.05 for students' environmental care attitude.